(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To evaluate the results and safety of ultrasound-guided MDs shoulder injection in the treatment of supraspinatus tendonitis at Thai Binh Medical University Hospital. Method: Descriptive, longitudinal, non-controlled study. Each patient received 2 ml of MDs Shoulder collagen (1 vial per session) injected into the subacromial bursa under ultrasound guidance, for a total of 5 consecutive injections, one week apart. The parameters to evaluate the effectiveness of MD Shoulder collagen injection therapy include improving pain levels on the VAS scale, improving shoulder joint motor function on the OSS scale, abduction angle of shoulder and ultrasound imaging. Parameters to evaluate the adverse effects of the therapy. Firstly, local manifestations include increased pain after injection, infection at the injection site, bleeding. Secondly, whole body manifestations include changing in pulse and blood pressure, headache, dizziness, nausea, vomiting, itching, shock. Assessment time points: pre-treatment (T0), 1-week post-treatment (T1), 4 weeks post-treatment (T4), and 12 weeks post-treatment (T12). Results: The therapy of ultrasound-guided MDs shoulder injection for supraspinatus tendonitis obtained the following results: the therapy improves VAS pain scores from week 4 and week 12, OSS function scores from week 4 and week 12, abduction angle of shoulder from week 1, week 4, and week 12; reduces hypoechoic rate on ultrasound by week 12. Regarding adverse effects, no whole-body adverse effects or serious complications were observed during the 3-month follow-up. Increased pain at the injection site occurred in 11.4% of cases. Conclusion: The therapy of ultrasound-guided MDs shoulder injection for supraspinatus tendonitis obtained the following results: the therapy improves VAS pain scores from week 4 and week 12, OSS function scores from week 4 and week 12, abduction angle of shoulder from week 1, week 4, and week 12; reduces hypoechoic rate on ultrasound by week 12. Regarding adverse effects, no whole-body adverse effects or serious complications were observed during the 3-month follow-up. Increased pain at the injection site occurred in 11.4% of cases.